2022
DOI: 10.1128/iai.00451-21
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Site-Specific Carbohydrate Availability Impacts Streptococcus pneumoniae Virulence and Fitness during Colonization and Disease

Abstract: Streptococcus pneumoniae ( Spn ) colonizes the nasopharynx asymptomatically but can also cause severe life-threatening disease. Importantly, stark differences in carbohydrate availability exist between the nasopharynx and invasive disease sites, such as the bloodstream, which most likely impact Spn ’s behavior. Herein, using chemically-defined media (CDM) supplemented with physiological levels of carbohydrates, we examined how anatomical-site specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Carbon availability has been shown to influence the 3 fermentation pathways and the production of pneumococcal virulence determinants [25], especially capsular polysaccharide [24]. We observed that all Spn mutants in our panel produced significantly less capsular polysaccharide than WT.…”
Section: Nad+/nadh Redox Imbalance Influences the Production Of Spn V...mentioning
confidence: 51%
See 1 more Smart Citation
“…Carbon availability has been shown to influence the 3 fermentation pathways and the production of pneumococcal virulence determinants [25], especially capsular polysaccharide [24]. We observed that all Spn mutants in our panel produced significantly less capsular polysaccharide than WT.…”
Section: Nad+/nadh Redox Imbalance Influences the Production Of Spn V...mentioning
confidence: 51%
“…Doubling time was not impaired once bacteria reached exponential phase, with ΔpdhC observed to replicate faster than WT. Importantly, all of the revertant strains had phenotypes equivalent to WT, indicating that observations made with our mutants were not due to off-target effects (S1 Fig) . Finally, to further dissect the divergence between the observed extended lag phase and unimpaired exponential phase of our mutants, we measured metabolic activity using heat flow [24]. With exception to the ldh mutant, none of the mutants in our panel displayed changes in…”
Section: Nad+/nadh Imbalance Alters the Spn Energy Poolmentioning
confidence: 99%
“…pspA expression was repressed when the response regulator RR06 was phosphorylated and overexpressed (Standish et al, 2007). A recent report by Im et al also showed pspA gene expression is influenced by carbon-catabolite repression and nutrient availability (Im et al, 2021). Altogether, one can infer that the regulation of pspA is multifaceted and complex.…”
Section: Pspa Regulationmentioning
confidence: 86%
“…A recent report by Im et al. also showed pspA gene expression is influenced by carbon-catabolite repression and nutrient availability ( Im et al., 2021 ). Altogether, one can infer that the regulation of pspA is multifaceted and complex.…”
Section: Established Roles For Pspa In Pneumococcal Virulencementioning
confidence: 95%
“…The capability to catabolize these sugars enables pneumococcus to survive in distinct host niches and invade into hosts ( 12 , 13 ). Therefore, the regulatory mechanisms in carbohydrate metabolism play important roles in the transition of pneumococcus from commensal to pathogenic status ( 14 ).…”
Section: Introductionmentioning
confidence: 99%